Age estimation from computed tomography of cranial suture closure in a Thai population - Sittiporn R,; Nuttaya P,; Sukon P,; Pasuk Mahakkanukrauh, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Age estimation from human skeletal remains is an important step to reconstruct a biological profile. Cranial suture has long been studied for its age-related closure. However, until now, forensic anthropologists still attempt to investigate the best way of estimating age at death from cranial suture closure because skull is usually found at the crime scene due to its easy recognised-appearance and persistence to post-mortem insults. For these reasons, a study of age estimation from cranial suture closure in a Thai population was conducted, which focussed to study the appearance and visibility of facial suture closure using computed tomography (CT). CT image series of 140 cases were obtained in order to investigate ectocranial closure of the selected facial sutures. The results from CT image analysis revealed that nasomaxillary provided the most consistent examination of suture closure (52%) while frontonasal delivered the lowest consistency in suture closure examination (29%). The inconsistency mostly occurred in assigning the closure score of 1 and 2. Thus, it could be suggested that a 3-scale scoring system of closure: open, closing, and closed, could be an appropriate method of evaluating degree of ectocranial closure of facial sutures obtained from CT imaging. This fundamental information of facial suture closure from CT images could serve as a starting point on development of age estimation technique from suture closure by utilising CT images.